Perancangan Aplikasi Enkripsi Pada File Suara Menggunakan Algoritma Spritz - Deni Anggara (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Issues Security and confidentiality of data is one important aspect in terms of information exchange. One solution to maintain security and confidentiality in the process of sending files with encryption techniques as encryption keys on voice files. This study describes developing cryptography (encryption and decryption) that applies the Spritz algorithm. But not all developments in communication technology have a positive and beneficial impact. One of the negative effects of sound files is data tapping, which is one of the most feared problems by network users and voice files. This research resulted in an application program aimed at preventing the security of sound files on storage media. in making this application, the method used is the Spritz algorithm, because it is very suitable for the security of voice files that result in the completion of the encryption and decryption process. This application was created with visual basic 2008 software and the creation of a file security application using encryption and decryption processes using the Spritz algorithm is expected to overcome these problems. The format used in making this application encrypts and decrypts the sound files that have an extension. WAP, and MP3